Personality, social support and risk-taking/antisocial behaviour: a study of their interactions - Bull, Sophie (2018)
Substantial literature suggests there is a relationship between core dimensions of personality, Dark Triad traits of personality, and risk-taking and antisocial behaviour. Social support has also been implicated as a protective factor against anti-social behaviour, risk-taking, and recidivism. This study aims to extend this previous research by investigating whether social support moderates the relationship between personality and behaviour. Self-report questionnaire scales were used to measure core dimensions of personality, Dark Triad Traits of personality, perceived social support, risk-taking behaviour, and antisocial behaviour. Using a sample of 439 persons from the general population, regression analyses in the current research demonstrate risk-taking behaviour is predicted by psychopathy, Machiavellianism, emotionality, and openness, whereas antisocial behaviour is predicted by psychopathy, openness, emotionality, and honesty-humility. Analyses show the perceived level of social support from family is weakly associated with less antisocial but not risk taking behaviour. No interaction effects were found for social support and personality on the outcome variables, suggesting no moderation effects. Results are discussed in relation to existing literature and limitations and avenues for future research are considered.